Aplicación de la norma internacional de contabilidad NIC 38: estudio del caso práctico de la empresa Universitaria S.A. - Ramirez Leon, Morelia Carolina (My University, 2019)
After the implementation of the International Accounting Standards (NIC) in Ecuador, many questions arose in the accountants regarding the application of a whole set of regulations that was eminently new for all professionals, since they worked in this area. Then with the Ecuadorian Accounting Standards (NEC), it is with this that the inconvenience arises, because the current regulations have another context, is created with paragraphs that are infinite and with too technical language that the average professional cannot understand. To apply the NICs, the Superintendence of Companies and the Internal Revenue Service, they organized free courses and also the professionals who have become aware, by their own means, have been trained, this has allowed them to demonstrate in the accounts that they report in the financial statements at fair value. This is the case of IAS 38, which is an exclusive rule for intangible assets, which have a great connotation and many problems in their application, in the present case study only a small part of the rule is addressed in which It allows to recognize it as an intangible asset, but it should be noted that the application is correct because it takes a tour of the theoretical bases of the paragraphs contained in this rule. It is also considered the study of the art of research that has been carried out in the last five years.
Luego de que en el Ecuador se implementaron las Normas Internacionales de Contabilidad (NIC), en los contadores(as) surgieron muchas interrogantes en cuanto a la aplicación de toda una normativa que era eminentemente nueva para todos los profesionales, ya que estos laboraban en ese entonces con las Normas Ecuatorianas de Contabilidad (NEC), es con ello que surge el inconveniente, porque la normativa vigente tiene otro contexto, está creada con párrafos que son infinitos y con un lenguaje demasiado técnico, que el profesional medio no lo puede comprender. Para aplicar las NIC, la Superintendencia de Compañías y el Servicio de Rentas Internas, organizaron cursos gratuitos y también los profesionales que han tomaron conciencia, por sus propios medios se han capacitado, esto les ha permitido demostrar en las cuentas que reportan en los estados financieros a valor razonable. Este es el caso de la NIC 38, que es una norma exclusiva para los (AI), que tienen una gran connotación y muchos problemas en su aplicación, en el presente estudio de caso se aborda solo una pequeña parte de la norma en la cual no permite reconocerlo como activo intangible, pero cabe señalar que la aplicación es correcta porque se hace un recorrido de las bases teóricas de los párrafos que contiene esta norma. También se considera el estudio del arte de investigaciones que se han realizado en los últimos cinco años.
Keywords: NIC 38; ACTIVO INTANGIBLE; FLUJO DE EFECTIVO; RECONOCIMIENTO DEL INTANGIBLE